If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 7 = 12y + -9 Reorder the terms: 7 + 8y = 12y + -9 Reorder the terms: 7 + 8y = -9 + 12y Solving 7 + 8y = -9 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 7 + 8y + -12y = -9 + 12y + -12y Combine like terms: 8y + -12y = -4y 7 + -4y = -9 + 12y + -12y Combine like terms: 12y + -12y = 0 7 + -4y = -9 + 0 7 + -4y = -9 Add '-7' to each side of the equation. 7 + -7 + -4y = -9 + -7 Combine like terms: 7 + -7 = 0 0 + -4y = -9 + -7 -4y = -9 + -7 Combine like terms: -9 + -7 = -16 -4y = -16 Divide each side by '-4'. y = 4 Simplifying y = 4
| 8+b=2-2b | | 3x=2x-5 | | s-31=-45 | | 19m=6 | | r+8=18 | | 2x+106=c | | 4.7m-6=3.9[m+2.2] | | 7y-3(y+6)=-10 | | 2y+5=-6y | | y^3=6y^2 | | -3x+2=y | | (2c+6)(2c-6)= | | y^2-18y-81=0 | | x^2-3x+2=y | | 2x^2-5=9x | | 4p+7=11+3p | | 16y^2+9x^2=144 | | 45=(2x+1)(x+1) | | 5+12x=x | | 2.5n=17.5 | | x^2-15x-28=0 | | -7s=63 | | 5a+5(6)=10 | | -2x+7=13x-5 | | -5y+5=-8y | | -150=-x^2-10 | | 10-3n=12n+1 | | r+3=22 | | 8y^2+5y-3=0 | | 7x=4[y+4] | | 649-x=260 | | -x^2-6x+10=0 |